2008
DOI: 10.1093/cvr/cvn079
|View full text |Cite
|
Sign up to set email alerts
|

FK506 can activate transforming growth factor-  signalling in vascular smooth muscle cells and promote proliferation

Abstract: FK506 can act as a growth factor for VSMCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 40 publications
3
37
0
Order By: Relevance
“…As shown in Fig. 4, top row, cells without FK506 treatment show a certain degree of ALK1/FKBP12 colocalization, a similar result as reported by Giordano et al (2008), in vascular smooth muscle cells with FKBP12 and the ubiquitous type I receptor ALK5. As shown by these authors, FKBP12 is an inhibitor of TGF-␤1 receptor type I ALK5 in myoblasts.…”
Section: Fk506 Increases Endoglin and Alk1 Expression 837supporting
confidence: 86%
See 3 more Smart Citations
“…As shown in Fig. 4, top row, cells without FK506 treatment show a certain degree of ALK1/FKBP12 colocalization, a similar result as reported by Giordano et al (2008), in vascular smooth muscle cells with FKBP12 and the ubiquitous type I receptor ALK5. As shown by these authors, FKBP12 is an inhibitor of TGF-␤1 receptor type I ALK5 in myoblasts.…”
Section: Fk506 Increases Endoglin and Alk1 Expression 837supporting
confidence: 86%
“…In particular, FKBP12 is a natural inhibitor of TGF-␤1-mediated signaling; therefore, ligands, such as FK506, act as TGF-␤1 activators, competing with the FKBP12 for the TGF-␤1 receptors (Udina and Navarro, 2002). In fact, in a previous report, Giordano et al (2008) demonstrated that FK506 increases the phosphorylation of Smad2/3, sequestering FKBP12, a receptor type I inhibitor, in mouse VSMCs. In this work, we have described the action of FK506 in endothelial cells, in which it triggers activation through the endothelial-specific receptor type I, ALK1/Smad1/5/8, as demonstrated by ALK1-specific reporter activation of this pathway (BRE-luc), and the natural promoter regulated by this way, Id1.…”
Section: Fk506 Increases Endoglin and Alk1 Expression 841mentioning
confidence: 92%
See 2 more Smart Citations
“…Rapamycin induces VSMC differentiation by specific activation of the Akt2 isoform, promoting expression of contractile proteins (129). In fact, arachidonic acid, TGF-β, FK506, and leptin induce VSMC proliferation through PI3K-dependent activation of mTOR (130)(131)(132)(133). Thus, autophagy in VSMCs can confer both adaptive and maladaptive actions depending on the context.…”
Section: Autophagy In Vascular Remodelingmentioning
confidence: 99%